Policy Reform on Investment Climate: Case Analysis of Hangzhou - Yufei, Pu (Washington, DC: World Bank, 2012)
The reform of the investment climate in Hangzhou, China, was a long process that involved many players and groups. This comparative analysis describes the different waves of reform, the forces behind them, and the resulting effects. The study concludes that central government policy toward a market economy was a strong force in promoting the improvement of the investment climate and that the municipal government of Hangzhou played a key role by adopting a focusing on certain tasks while putting others aside policy. Whether the investment climate is good or bad has a strong impact on the economic development of the region.